1979
DOI: 10.1001/archderm.115.6.734
|View full text |Cite
|
Sign up to set email alerts
|

Yellow nail syndrome. Possible association with malignancy

Abstract: A dramatic resolution of yellow nail deformity occurred in a 66-year-old man shortly after the removal of a carcinoma of the larynx. Seventeen months later, a productive cough developed and radiologic evidence of bronchiectasis was found. There was no evidence of lymphedema, pleural effusion, sinusitis, or immunologic abnormalities. At least three other patients with a variant of yellow nail syndrome have died of malignancy. Therefore, the resolution of the nail deformity following laryngectomy may not be fort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0
1

Year Published

1989
1989
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 0 publications
0
24
0
1
Order By: Relevance
“…YNS has been associated with other conditions including autoimmune disorders, 4 immunodeficiency states, 17,18 nephrotic syndrome, 19 Guillain-Barre syndrome, 20 drugs (D-penicillamine, gold) and cancers. 4,6,17,19,[21][22][23][24][25][26][27][28] Three of our patients had a history of malignancy. YNS has also been reportedly associated with lymphopenia, low IgA levels and hypogammaglobulinaemia.…”
Section: Discussionmentioning
confidence: 99%
“…YNS has been associated with other conditions including autoimmune disorders, 4 immunodeficiency states, 17,18 nephrotic syndrome, 19 Guillain-Barre syndrome, 20 drugs (D-penicillamine, gold) and cancers. 4,6,17,19,[21][22][23][24][25][26][27][28] Three of our patients had a history of malignancy. YNS has also been reportedly associated with lymphopenia, low IgA levels and hypogammaglobulinaemia.…”
Section: Discussionmentioning
confidence: 99%
“…YNS has been related to malignancies, including mycosis fungoides, laryngeal carcinoma, gallbladder carcinoma, bronchial carcinoma, breast cancer, non-Hodgkin lymphoma, and endometrial cancer. In several reported cases, the nail deformity resolved after successful treatment of the associated neoplasm (81)(82)(83).…”
Section: Yellow Nail Syndromementioning
confidence: 99%
“…11,12 It has therefore been suggested that YNS may represent a paraneoplastic phenomenon. 13 In the original report, the authors stated that none of the patients had a positive family history (FH) of a similar condition. Since then, over 100 cases have been published, most of which have been sporadic.…”
mentioning
confidence: 99%